2020
DOI: 10.1111/gcbb.12731
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide quantitative trait loci detection for biofuel traits in switchgrass (Panicum virgatum L.)

Abstract: Lignocellulosic biomass is composed of complex structures of cellulose, hemicellulose, lignin, and other biochemical and structural components of cell wall. Because of its obligatory outcrossing nature, broad adaptation, and extensive genetic variation, both biomass production and cell wall composition traits could be improved for biofuel production. Among the cell wall components, lignin has been found to be a major inhibitor of the conversion process of cellulosic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In addition to evaluating the level and relevance of the intraspecific genetic variability of SQTLs in diverse species, another aim of this study was to assess the validity of SQTLs for predicting genomic loci associated with biomass quality traits in novel plant populations and species. This aspect was studied by assessing the degree of colocalization between the SQTLs previously detected in Miscanthus sinensis and Panicum virgatum [ 1 ] and cell wall related QTLs mapped by genome-wide association analysis (GWAS) in a Miscanthus sinensis collection and QTLs mapped by other researchers in an F1 progeny of a biparental cross of two switchgrass lines diverging for cell wall quality traits [ 21 ]. These populations represent respectively a different intraspecific population than the one from which QTLs used for SQTLs mapping came from (miscanthus), and a separate species than the ones from which initial QTLs have been selected at the moment of SQTLs detection (thus, a hypothetical novel, under-domesticated, species; switchgrass).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to evaluating the level and relevance of the intraspecific genetic variability of SQTLs in diverse species, another aim of this study was to assess the validity of SQTLs for predicting genomic loci associated with biomass quality traits in novel plant populations and species. This aspect was studied by assessing the degree of colocalization between the SQTLs previously detected in Miscanthus sinensis and Panicum virgatum [ 1 ] and cell wall related QTLs mapped by genome-wide association analysis (GWAS) in a Miscanthus sinensis collection and QTLs mapped by other researchers in an F1 progeny of a biparental cross of two switchgrass lines diverging for cell wall quality traits [ 21 ]. These populations represent respectively a different intraspecific population than the one from which QTLs used for SQTLs mapping came from (miscanthus), and a separate species than the ones from which initial QTLs have been selected at the moment of SQTLs detection (thus, a hypothetical novel, under-domesticated, species; switchgrass).…”
Section: Resultsmentioning
confidence: 99%
“…An analogous procedure to the one just described for miscanthus was performed in switchgrass to test the colocalization between the 56 cell wall-related QTLs identified by Ali, Serba, Walker, Jenkins, Schmutz, Bhamidimarri, and Saha [ 21 ] ( Supplementary Table S5 ), and the 254 SQTLs previously detected in switchgrass and conserved across Poaceae ( Supplementary Table S6 ). In switchgrass, it was shown that 53 SQTLs (20.8% of all the switchgrass SQTLs) (partially) colocalize with the 56 cell wall QTLs, while 33 QTLs (59%) colocalize for >50% of their length with SQTLs ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations